Judaism and World Religions - Brill, A. author. aut Link
XVII, 306 p.
Keywords: Provides the first extensive collection of traditional and academic Jewish approaches to the religions of the world, focusing on those Jewish thinkers that actually encounter the other world religions -that is, it moves beyond the theory of inclusive/exclusive/pluralistic categories and looks at Judaism's interactions with other faiths.